Knuckles notifications: mid-air haptic feedback on the dorsal hand for hands-on-the-wheel driving - Montano, Roberto; Morales, Rafael; Pittera, Dario; Frier, William; Georgiou, Orestis; Cornelio, Patricia (Frontiers in Computer Science, 2024)
Ultrasound-based mid-air haptic feedback has been demonstrated to be an effective way to receive in-vehicle information while reducing the driver's distraction. An important feature in communication between a driver and a car is receiving notifications (e.g., a warning alert). However, current configurations are not suitable for receiving notifications (haptic device on the center console requiring palmar feedback) as they force the driver to take their hands off-the-wheel and eyes off-the-road. In this paper, we propose “knuckles notifications,” a novel system that provides mid-air haptic notifications on the driver's dorsal hand while holding the steering wheel. We conducted a series of exploratory studies with engineers and UX designers to understand the perceptual space of the dorsal hand and design sensations associated with 4 in-car notifications (incoming call, incoming text message, navigation alert and driver assistant warning). We evaluated our system with driver participants and demonstrated that knuckles notifications were easily recognized (94% success rate) while not affecting the driving task, and mid-air sensations were not masked by background vibration simulating the car movement.